Long COVID-19 alters muscle architecture and muscle-tendon force transmission: a one-year longitudinal study - Leandro Gomes de Jesus Ferreira; Leandro Gomes de Jesus Ferreira; Isabella da Silva Almeida; Isabella da Silva Almeida; Rochelle Rocha Costa; Gabrielle Vieira Roriz; Gabrielle Vieira Roriz; Jeam Marcel Geremia; João Luiz Quagliotti Durigan; João Luiz Quagliotti Durigan; Rita de Cássia Marqueti; Rita de Cássia Marqueti (Frontiers in Physiology)
IntroductionThere are limited studies on the long-term effects of COVID-19 on skeletal muscle morphology and architecture. Therefore, this study aims to address this gap by assessing the effects of prior COVID-19 infection on quadriceps muscle architecture and tendon-aponeurosis complex (TAC) properties over a one-year period, comparing three cohorts: individuals with moderate COVID-19, individuals with severe COVID-19, and a healthy control group.MethodsSeventy participants were included in the study and allocated to three groups: moderate COVID-19 (n = 22), severe COVID-19 (n = 18), and control (n = 30). Four assessments were conducted over 1 year for the COVID groups. Maximal voluntary isometric (MVIC) knee extension contractions were performed on an isometric dynamometer, with simultaneous ultrasound imaging of the vastus lateralis (VL) and rectus femoris (RF) muscles. Fascicle length (FL) and pennation angle (PA) were obtained at rest and during MVIC, along with TAC displacement. Generalized Estimating Equation models were used to evaluate muscle variables, with “group” and “time” as factors. The model fit was adjusted, with ‘torque’ as a covariate.ResultsRegarding muscle architecture, FL was greater in the severe COVID-19 group during early post-infection assessments for the RF at rest (p = 0.043). Additionally, both COVID-19 groups exhibited longer VL fascicles compared to controls (p = 0.032). TAC displacement was reduced in the severe COVID-19 group (RF: p = 0.008; VL: p = 0.047) compared to control. TAC stiffness did not differ between groups (p = 0.517), but torque production demonstrated an effect on this variable (p = 0.001). Both COVID-19 groups presented reduced PA for the VL at rest (p = 0.012) compared to control. Additionally, torque played a crucial role in influencing PA in both muscles, at rest and during contraction.ConclusionParticipants with severe COVID-19 exhibited alterations in muscle architecture, which may contribute to persistent muscular weakness even one-year post-infection. The findings underscore the potential role of muscle strength, particularly the impact of torque on TAC stiffness and PA across all groups. Long COVID-19 rehabilitation and exercise physiologists should prioritize quadriceps strengthening strategies to restore muscle architecture and optimize force transmission.